ANALISIS PENERIMAAN E-PERFORMANCE PADA PEGAWAI DINAS KOPERASI DAN UMKM SURABAYA MENGGUNAKAN METODE TECHNOLOGY ACCEPTANCE MODEL 2 - rifatul Fithri; Sulistiowati Sulistiowati; Puspita Kartikasari (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Dinas Koperasi and UMKM Surabaya currently uses E-Perfomance application to measure employee performance appraisal and monitor the activities of employees. The E-Perfomance application is used starting in 2015 and made many changes every year. Since the beginning of the use of E-Perfomance application until now has not been evaluated the acceptance in applying the application. Therefore, in this research, there is an acceptance analysis of E-Performance application with Technology Acceptance Model 2 method consisting of Subjective Norm Norm, Image, Job Relevance, Output Quality, Result Demonstrability as independent variable, while dependent variable include Perceived Usefulness, Perceived Ease of Use, Intention to Use, Usage Behavior and moderation variables include Experience variables.